3D-cultured hADSCs-derived exosomes deliver circ_0011129 to synergistically attenuate skin photoaging - Zhang, Yu; Zhou, Feng; Nie, Gang; Li, Liang; Wen, Juan; He, Shimin; Yao, Amin (Frontiers in Genetics, 2025)
BackgroundSkin photoaging is primarily induced by ultraviolet (UV) exposure, involving mechanisms such as reactive oxygen species (ROS) accumulation, matrix metalloproteinase (MMP)-mediated collagen degradation, and cathepsin (e.g., Cathepsin K)-driven elastin denaturation and aggregation. Although circular RNA (circRNA) shows significant potential in regulating skin photoaging, its clinical translation remains challenging due to poor in vivo stability and targeted delivery efficiency.ObjectiveThis study aimed to construct a 3D-cultured human adipose-derived mesenchymal stem cell (hADSC)-derived exosome (3D-Exo) loaded with circ_0011129 (3D-circ-Exo) and investigate its protective effects and molecular mechanisms against chronic UV-induced damage in human dermal fibroblasts (HDFs).MethodsA circ_0011129-overexpressing hADSC cell line was established via lentiviral transfection. Exosomes were isolated, and circRNA integrity was validated through divergent/convergent primer amplification, sequencing, and RNase R digestion. A chronic photoaging HDFs model was induced by 7-day UVA irradiation (5 J/cm2/d). Cellular senescence (SA-β-gal staining, p53/p21/p16 expression) and extracellular matrix degradation (collagen I, elastin) were assessed. Therapeutic effects were evaluated across four groups: light-shielded control, UVA-irradiated control, 3D-Exo + UV, and 3D-circ-Exo + UV.ResultsThe 3D-circ-Exo carrier successfully encapsulated circ_0011129 with a closed circular structure and significantly higher stability than linear RNA (p < 0.001). In the chronic photoaging model, UVA irradiation increased SA-β-gal-positive cells (p < 0.01), upregulated p53/p21/p16 protein expression (p < 0.01), and reduced collagen I and elastin levels (p < 0.001). Compared to 3D-Exo, 3D-circ-Exo demonstrated superior anti-photoaging effects: reduced SA-β-gal-positive cells (p < 0.05), downregulated p53/p21/p16 (p < 0.01), and restored collagen I/elastin expression (p < 0.01), significantly outperforming 3D-Exo.ConclusionBy integrating 3D culture with exosome delivery technology, this study constructed a functionalized circ_0011129 carrier (3D-circ-Exo) for the first time. 3D-circ-Exo significantly enhances anti-photoaging efficacy compared to 3D-Exo, suggesting that 3D-cultured exosomes synergize with circ_0011129 to inhibit cell cycle arrest (p53/p21/p16) and counteract UV-induced collagen loss and elastin denaturation. This work provides an innovative strategy for clinical photoaging intervention.